Republican learning : John Toland and the crisis of Christian culture, 1696-1722 - Champion, Justin (Politics, culture, and society in early modern Britain., 2003)
This work explores the life, thought and political commitments of free-thinker John Toland (1670-1722). Studying both his private archive and published works, it illustrates how Toland moved in both subversive and elite political circles in England and abroad.